A new species of the genus Paratus Simon (Araneae: Liocranidae) from Thailand - Zapata, Lorena V.; Ramírez, Martín J. (Zootaxa, 2010)
The spider genus Paratus Simon, 1898 was recently revised by Marusik et al. (2008). It comprises squat spiders with a high, almost round carapace strongly narrowed in front, uniform leg length, anterior tibiae and metatarsi with several pairs of strong ventral spines and some lateral spines, and abdomen almost globular. The genus was placed with some hesitation in Liocranidae by Marusik et al. (2008), in its own subfamily, Paratinae. Only three species have been described in the genus, all known from a few samples from the type locality or nearby areas: P. reticulatus Simon, 1898 from Sri Lanka is known only from the female holotype (Deeleman-Reinhold 2001). Paratus sinensis and P. indicus, from China and India respectively, were recently described based on a few specimens of both sexes (Marusik et al. 2008). It seems that Paratus species are very rare in collections, as Deeleman-Reinhold had access to intensive samplings of spiders in regions where the genus occurs.